Moisture Susceptibility of Asphalt Concrete Pavement Modified by Nanoclay Additive - Saif Al-din Majid Ismael; Mohammed Qadir Ismael (Salehan Institute of Higher Education, 2019)
Durability of hot mix asphalt (HMA) against moisture damage is mostly related to asphalt-aggregate adhesion. The objective of this work is to find the effect of nanoclay with montmorillonite (MMT) on Marshall properties and moisture susceptibility of asphalt mixture. Two types of asphalt cement, AC(40-50) and AC(60-70) were modified with 2%, 4% and 6% of Iraqi nanoclay with montmorillonite. The Marshall properties, Tensile strength ratio(TSR) and Index of retained strength(ISR) were determined in this work. The total number of specimens was 216 and the optimum asphalt content was 4.91% and 5% for asphalt cement (40-50) and (60-70) respectively. The results showed that the modification of asphalt cement with MMT led to increase Marshall stability and the addition of 6% of MMT recorded the highest increase, where it increased by 26.35% and 22.26% foe asphalt cement(40-5) and(60-70) respectively. Also, the addition of MMT led to increase moisture resistance of asphalt mixture according to the increase in TSR and IRS. The addition of 4% and 6% of MMT recorded the highest increase in TSR and IRS for asphalt cement (40-50) and (60-70) respectively, where they increased by 11.8% and 17.5% respectively for asphalt cement (40-50) and by 10% and 18% respectively for asphalt cement (60-70).